The Linares Addictive Potential Model - Oscar A. Linares (Journal of Pharmacy and Nutrition Sciences, 2012)
The Salerian Addictive Potential (SAP) hypothesis indicates that addictive potential may be calculated as A=E/Tmax x t1/2, where A is addictive potency, E euphoric potency, Tmax (hr) is the time to reach peak plasma concentration, and t½ (hr) is the plasma elimination half-life. However, this approach is inconsistent with first-order linear pharmacokinetics. The units of the denominator of the equation are units of acceleration (hr2), not speed (the first derivative). Therefore, the present contribution presents a minimal-model hypothesis for quantifying a drug's addictive potential. This model is superior to the SAP model because it is the simplest model, with the minimum number of parameters and assumptions, and it decreases variance through less loss of information.